(3GdeMGSHI aj TQcGJ GdCTNGU (B/s - (3GdUMf, YHOGdaJGM eMeOs ((3GdEScfOQjI(B: s (3bSe GdeMGSHI hGdeQGLYI(B, s, 2000)
(3Jchjf GdTQcI heYGdLI GdeMGSHI dMUU QCS GdeGd ,JhRjY GdCQHGM hGdMSGHGJ GdNJGejI aj TQcGJ GdCTNGU ,JYOjd YbO GdTQcI ,JUajI TQcGJ GdCTNGU ,GdJUajI GdJOQjLjI GdEfOeGL aj TQcGJ GdCTNGU hGdNGUIs
Keywords: (3GdeMGSHIs; (3GdeMGSHI (B- (3TQcGJs